Weekday and outcomes of elective cardiac surgery in the UK: a large retrospective database analysis. (29th January 2022) - Fudulu, Daniel Paul; Dimagli, Arnaldo; Sinha, Shubhra; Narayan, Pradeep; Chan, Jeremy; Dong, Tim; Benedetto, Umberto; Angelini, Gianni Davide
Abstract: OBJECTIVES: Several studies have shown worse outcomes in patients operated on later in the week. We tested this hypothesis in a large UK national audit database in elective patients undergoing adult cardiac surgery. METHODS: We used a generalized additive model to evaluate the effect of the day of the week on the following postoperative outcomes: 30-day mortality, stroke, need for dialysis and return to theatre for bleeding. We have adjusted for the relevant European System for Cardiac Operative Risk Evaluation (EuroSCORE) II covariates, plus responsible consultant, hospital and year of operation and performed subgroup analysis for isolated coronary artery bypass grafting (CABG) procedures. RESULTS: Out of 371 500 patients, 60 555 (16.3%) underwent AVR, 36 553 (9.8%) AVR plus CABG, 238 812 (64.3%) isolated CABG, 26 517 (7.1%) isolated mitral valve repair or replacement and 9063 (2.4%) mitral valve plus CABG. A total of 13 997 (3%) had surgery over the weekend. After covariate adjustment, we found no effect of day of surgery on mortality ( P  = 0.081), stroke ( P  = 0.137) and need for postop dialysis ( P  = 0.732). However, across all operations, there was evidence of a lower rate of return to theatre for bleeding/tamponade at the weekend ( P  = 0.039). In subgroup analysis of isolated CABG, the day of the week did not affect any outcomes. CONCLUSIONS: We found no effect of the day of the week on risk-adjusted short-term mortality, stroke, and the requirement for postoperative dialysis after elective cardiac surgery. Overall, the patients operated on during the weekdays were less likely to return to theatre for bleeding. In isolated CABG, the day of the week did not affect any outcomes. Abstract : More than a decade ago, several studies argued for a higher mortality rate for weekend admissions [1–4].